Pelatihan Strategi Komunikasi Efektif untuk Implementasi Parenting pada Orang Tua Wali Siswa Taman Kanak-Kanak di Sleman - Chatia Hastasari (Jurnal Pengabdian Pada Masyarakat, 2020)
EFFECTIVE COMMUNICATION STRATEGY TRAINING FOR PARENTING IMPLEMENTATION OF PARENTS OF KINDERGARTEN STUDENTS IN SLEMAN. This Community Service activity aims to (1) increase knowledge, understanding and appreciation of children's development in terms of physical, psychological, social and moral (Early Childhood) along with solutions to problems that arise; Parenting style, context and family resilience and (2) increase knowledge, understanding and appreciation of effective family communication. The target audience for this PPM activity is 30 parents (both fathers and mothers) in Pertiwi I Sumber Sumber Kindergarten and Indriyasana 3 Mlati Sleman Kindergarten. While the method of activities undertaken are lectures, discussions and evaluations. Monitoring and Evaluation conducted in this service is by asking participants to fill in an evaluation instrument containing a self-evaluation which must be submitted two weeks after the training.